A Improving the Skills of Making Gamis for PKK Mothers in Jati Village Karanganyar Regency: Peningkatkan Ketrampilan Pembuatan Baju Gamis bagi Ibu PKK di Desa Jati Kabupaten Karanganyar - Eem Kurniasih (Join, 2022)
In increasing the family income of PKK women, Dk. Ocak-Acik RT.01 and RT.02, Jati, Jaten Karanganyar-Surakarta, This training activity aims to increase the skills of sewing clothes that can increase family income, towards a prosperous family. The implementation of this community service will last for 6 months by optimizing counseling and training programs with an andragogy training model, which is 90% practice and 10% theory. Participants focus more on the practice of breaking the model from the basic pattern to the pattern that has been adapted to the respective model that has been chosen by the partner. Optimizing the program, among others, by making women's clothing, namely Gamis clothing. Provide advanced training workshops in community empowerment which include making Muslim clothing by making dresses that are sewn by operating a sewing machine. The target to be achieved in this program is to increase household income and the skills of PKK women about making Muslim clothing, namely Gamis clothing as the development of making basic level patterns, while the desired output is PKK women can produce Muslim clothing in the form of Gamis clothing that can marketed in all areas of Semarang and Surakarta. From these activities, the entire family of the partners can be economically prosperous.